A talk on deliotte tax challenge - Ch'ng, Looi Chin (UiTM Sarawak, 2016)
A talk on Deloitte Tax Challenge was conducted on Friday, 25th September 201 5 from 2.00 pm until 4.30 pm at Dewan Kuliah 3, Block M. It was a programme held for the accounting students in Sarawak by Deloitte Tax Services Sdn Bhd. The purpose of the talk was to brief the students about the competition and encourage them to enrol